Effect of an α-calcium sulfate hemihydrate/treated dentin matrix composite to regenerate bone in critically sized SD rat calvarial defects - Wang, Mengmeng; Li, Bingyan; Li, Wenshuai; Hu, Zelong; Fu, Haojie; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2024)
Although α-calcium sulphate hemihydrate(α-CSH) has been widely used as an artificial bone graft material, it has several drawbacks, such as quick deterioration and limited osteoinductivity. Extensive research is now being conducted to produce advanced biomaterials based on α-CSH that has enhanced osteogenic properties for the healing of bone deformities. The aim of this work was to create a mixture of treated dentin matrix (TDM) and α-CSH to produce composite cements, and then examine their potential to promote the development of new bone in rats with critical-sized calvaria bone lesions. The characteristics of TDM /α-CSH composites were assessed using a universal mechanical testing machine, scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The biological characteristics of TDM /α-CSH composites were investigated by measuring the development and proliferation of osteoblasts using the CCK-8 test. In addition, the cements were implemented in the restoration of calvaria bone defects in rodents. The results of our study indicated that the compressive strength of the TDM/α-CSH cements exhibited a decline as the TDM mass ratio increased. Upon thorough mixing, the scanning electron microscopy analysis revealed that TDM/α-CSH had a distinct three-dimensional porous network structure and a notable enhancement in surface roughness. The XRD and FT-IR studies confirmed that the combination of the two materials resulted in a physical mixture, and the composition of the phases in the composites remained unchanged. The TDM/α-CSH composites demonstrated a significant stimulatory effect on osteoblast proliferation, which was dependent on the amount of TDM incorporated. Furthermore, in an in vivo experiment using a calvarial bone defect model, TDM/α-CSH cements exhibited superior enhancement of new bone formation, as confirmed by X-ray examination and μ-CT analysis. These findings suggest that TDM/α-CSH composite cements have promising potential as an alternative for repairing bone defects.